FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK KONVENSIONAL PADA BURSA EFEK INDONESIA - Debbi Chyntia Ovami (Universitas Medan Area, 2017)
The objective of the research was to analyze the influence of the factors of capital adequacy ratio, third-party funds, non perfoming loan, operating expense and operating revenue and loan to deposit ratio simultaneously and partially on the financial performance. The population was 41 conventional bank listed in the Indonesia Stock Exchange from 2010 to 2014, and 20 were used as the samples, using purposive sampling technique. The data were processed by using multiple linear regression tests with an SPSS software program. The result of the research showed that capital adequacy ratio, third-party funds, non perfoming loan, operating expense and operating revenue and loan to deposit ratio simultaneously on the financial performance. Partially, capital adequacy ratio had positive and significant influence on the financial performance, operating expense and operating revenue had negative and significant influence on the financial performance while third-party funds, non perfoming loan and loan to deposit ratio did not have any significant influence.Keywords: capital adequacy ratio, third-party funds, non perfoming loan, operating expense and operating revenue, loan to deposit ratio, financial performance